Transport Numbers and Electroosmosis in Cation-Exchange Membranes with Aqueous Electrolyte Solutions of HCl, LiCl, NaCl, KCl, MgCl2, CaCl2 and NH4Cl - Simon B. B. Solberg; Zelalem B. Deress; Marte H. Hvamstad; Odne S. Burheim (Entropy)
Electroosmosis reduces the available energy from ion transport arising due to concentration gradients across ion-exchange membranes. This work builds on previous efforts to describe the electroosmosis, the permselectivity and the apparent transport number of a membrane, and we show new measurements of concentration cells with the Selemion CMVN cation-exchange membrane and single-salt solutions of HCl, LiCl, NaCl, MgCl2, CaCl2 and NH4Cl. Ionic transport numbers and electroosmotic water transport relative to the membrane are efficiently obtained from a relatively new permselectivity analysis method. We find that the membrane can be described as perfectly selective towards the migration of the cation, and that <semantics>Cl−</semantics> does not contribute to the net electric current. For the investigated salts, we obtained water transference coefficients, <semantics>tw</semantics>, of 1.1 ± 0.8 for HCl, 9.2 ± 0.8 for LiCl, 4.9 ± 0.2 for NaCl, 3.7 ± 0.4 for KCl, 8.5 ± 0.5 for MgCl2, 6.2 ± 0.6 for CaCl2 and 3.8 ± 0.5 for NH4Cl. However, as the test compartment concentrations of LiCl, MgCl2 and CaCl2 increased past 3.5, 1.3 and 1.4 mol kg−1, respectively, the water transference coefficients appeared to decrease. The presented methods are generally useful for characterising concentration polarisation phenomena in electrochemistry, and may aid in the design of more efficient electrochemical cells.